Parafunctions, signs and symptoms of temporomandibular disorders (TMD) among adolescents 14 to 15 years of age - Urban, Magdalena; Suligowska, Klaudia; Wytrykowska, Anna; Prośba-Mackiewicz, Maria; Zdrojewski, Tomasz; Wrotkowska, Magdalena (Journal of Stomatology, 2017)
Introduction. Temporomandibular Joint Disorders (TMD) increasingly affect not only adults but also adolescents. Parafunctions are cited as the most common cause of TMD. Aim of the study. To determine the prevalence of oral parafunctions, signs and symptoms of TMD among adolescents. Methods. The study was performed as a part of an early detection of risk factors for civilization diseases program – SOPKARD1 in 96 children aged 14-15 years. Each participant filled in a questionnaire regarding their oral habits and symptoms of TMD and underwent physical examination of the muscles and temporomadibular joints. The analysis of the mandible mobility models was also made. Results. Leaning one’s chin on the hand (73.68%), lip biting (58.33%) and intensive gum chewing (51.04%) were the most common habits among the study group. Persistence of an infantile swallow pattern was observed in over one-fifth of patients (20.83%). The most common signs were teeth impressions on tongue and cheeks (53.13%), increased muscle tone (57.29%) and dysfunctions in mandibular mobility (53.13%). Most subjects (92.71%) manifested at least one sign or symptom, whereas 46.88% two or three. A statistically significant association was found between chewing gum and muscle response, as well as infantile swallow pattern and open bite and muscle response. Conclusions. Most adolescents aged 14-15 were subject to some parafunctional habits. There is a requirement to introduce an educational program in schools in order to present the destructive consequences of parafunctions on the stomatognathic system health and the possibility of prevention or treatment.